Evaluation and measurement of urban viability and factors affecting it (case study of Bojnourd city) - Mohammad Saghebi; Ezatollah mafi; Mehdi Watanparast (تحقیقات کاربردی علوم جغرافیایی)
Today, urban livability is the key concept in urban planning. At present, the concept of sustainable development and livability is one of the new concepts in developed countries. The city of Bojnourd has witnessed unequal urban spaces due to the increasing population growth, especially in the last three decades, so the necessity and importance of the issue of livability is quite evident in the city today. This study was developed with the aim of evaluating and measuring urban viability and the factors affecting it. The present study is applied in terms of purpose and descriptive-analytical in terms of method. In order to collect the required data and information, library and field methods and questionnaire tools were used. The statistical population of the study consists of citizens living in Bojnourd, the sample size was estimated 384 people using Cochranchr('39')s formula. In order to achieve the objectives of the study, one-sample t-test and linear regression were used in SPSS software. The results of this study showed that the situation of urban livability in Bojnourd, according to the general average obtained, which was equal to 2.75, is in a situation below the average. Also, in terms of the studied dimensions, the social dimension with an average of 2.84 has the highest average and the environmental dimension with an average of 2.67 has the lowest average. Also, the results of this study show that the situation in Region 2 is better than in Region 1 of Bojnourd. Other findings of this study include the positive effect of citizenschr('39') sense of security and health on urban livability.